2018
DOI: 10.4236/fns.2018.94033
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Diabetic Potential of Thermally Treated Garlic, Turmeric, and Ginger in Pre-Diabetic Male Wistar Rat Model

Abstract: Spices (turmeric (T), ginger (GI), and garlic (GA) (TGG)) have been used for centuries for food preservation, flavors, and medicinal properties. Research suggests that TGG contain potent antioxidants that may prevent and/or delay chronic diseases such as cancer, diabetes, and heart diseases. Heat treatment of spices may potentially increase antioxidative activity by modifying the inherent chemical structure of potent antioxidative compounds in spices. The purpose of this study was to determine the anti-diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Several natural herbal compounds were investigated for their protective and possible therapeutic effects against Cd-induced tissue damage ( Liu L. et al, 2015 ; Rafiee et al, 2019 ). Ginger extract has potent anti-inflammatory, antioxidant ( Arablou et al, 2014 ), and anti-diabetic properties ( Hester et al, 2018 ) comparable to pharmacological agents ( Marettová et al, 2015 ). Our study showed a significant protective effect of ginger administration on testicular functions as evidenced by reduced testicular-weight loss and higher plasma testosterone, FSH and LH levels compared to Cd-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several natural herbal compounds were investigated for their protective and possible therapeutic effects against Cd-induced tissue damage ( Liu L. et al, 2015 ; Rafiee et al, 2019 ). Ginger extract has potent anti-inflammatory, antioxidant ( Arablou et al, 2014 ), and anti-diabetic properties ( Hester et al, 2018 ) comparable to pharmacological agents ( Marettová et al, 2015 ). Our study showed a significant protective effect of ginger administration on testicular functions as evidenced by reduced testicular-weight loss and higher plasma testosterone, FSH and LH levels compared to Cd-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, thermally treated (toasted in conventional stove-top) spices (ginger- Zingiber officinale , garlic- Allium sativum , and turmeric- Curcuma longa ) showed high phenolic linked antioxidant and enhanced α-glucosidase enzyme inhibitory activity ( 116 ). In another study, Hester et al ( 115 ) found induced antioxidant activity in Wistar male rat following feeding with thermally treated garlic, ginger, and turmeric. Thermally treated onion ( Allium cepa ) extracts also showed improvement in anti-hyperglycemic functional qualities by suppressing carbohydrate absorption via inhibition of intestinal sucrose ( 117 ).…”
Section: Post-harvest Strategies To Improve Phenolic Bioactive-linked Antioxidant and Anti-diabetic Functionalities Of Plant-derived Foodmentioning
confidence: 95%
“…Turmeric, ginger, and garlic were found to be beneficial to the diet, and blood glucose levels were reduced when turmeric at 90mg/dL was fed versus the control group. [11] The insulin resistance, oxidative stress, biochemical parameters, and anthropometric results of 40 T2 D patients taking metformin and/or glibenclamide were evaluated with rosemary tea (2 g / 1 litre per day) as a supplementary therapy. This treatment is notable for lowering glycosylated hemoglobin percentage, insulin resistance, and pancreatic -cell function.…”
Section: Reduction Of Blood Glucose Level By Spices Compoundsmentioning
confidence: 99%